B cell lymphoma 6A regulates immune development and function in zebrafish - Almohaisen, Farooq L. J.; Heidary, Somayyeh; Sobah, Mohamed L.; Ward, Alister C.; Liongue, Clifford (Frontiers in Cellular and Infection Microbiology, 2022)
BCL6A is a transcriptional repressor implicated in the development and survival of B and T lymphoctyes, which is also highly expressed in many non-Hodgkin’s lymphomas, such as diffuse large B cell lymphoma and follicular lymphoma. Roles in other cell types, including macrophages and non-hematopoietic cells, have also been suggested but require further investigation. This study sought to identify and characterize zebrafish BCL6A and investigate its role in immune cell development and function, with a focus on early macrophages. Bioinformatics analysis identified a homologue for BCL6A (bcl6aa), as well as an additional fish-specific duplicate (bcl6ab) and a homologue for the closely-related BCL6B (bcl6b). The human BCL6A and zebrafish Bcl6aa proteins were highly conserved across the constituent BTB/POZ, PEST and zinc finger domains. Expression of bcl6aa during early zebrafish embryogenesis was observed in the lateral plate mesoderm, a site of early myeloid cell development, with later expression seen in the brain, eye and thymus. was observed in the lateral mesoderm. CRISPR/Cas9 genome editing was utilized to target the zebrafish bcl6aa gene. Homozygous bcl6aa mutants developed normally until around 14 days post fertilization (dpf), after which their subsequent growth and maturation was severely impacted along with their relative survival, with heterozygous bcl6aa mutants showing an intermediate phenotype. Analysis of immune cell development revealed significantly decreased lymphoid and macrophage cells in both homozygous and heterozygous bcl6aa mutants, being exacerbated in homozygous mutants. In contrast, the number of neutrophils was unaffected. Only the homozygous bcl6aa mutants showed decreased macrophage mobility in response to wounding and reduced ability to contain bacterial infection. Collectively, this suggests strong conservation of BCL6A across evolution, including a role in macrophage biology.